2006
DOI: 10.1080/10255840600980940
|View full text |Cite
|
Sign up to set email alerts
|

Finite element model of the human neck during omni-directional impacts. Part II: relation between cervical curvature and risk of injury

Abstract: A detailed 3D FE model of the human neck was used to assess a possible relationship between risk of injury and cervical spine curvature for various impacts. A FE model was previously developed, representing the head and neck of a 50th percentile human with a normal lordotic curvature. The model behaviour was omni-directionally validated for various impacts using published results. For the present study, the model was deformed in order to obtain a straight and a kyphotic curvature, and for each geometry, rear-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Intersegmental orientation and spinal curvature is highly variable between individuals and has a substantial role in individual disposition to neck and back injuries, including muscular fatigue or soft-tissue injuries, as well as more serious injuries related to hyperflexion and hyperextension (Coakwell et al, 2004; Frechede et al, 2006). Variation in intersegmental orientation and overall spinal curvature are modeled implicitly in the current SSM approach; however, explicitly modeling vertebral orientation and spinal curvature variables would allow the investigation of the role and interaction of vertebral morphology, intersegmental orientation, and spinal curvature variables on the likelihood of injury under various loading conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intersegmental orientation and spinal curvature is highly variable between individuals and has a substantial role in individual disposition to neck and back injuries, including muscular fatigue or soft-tissue injuries, as well as more serious injuries related to hyperflexion and hyperextension (Coakwell et al, 2004; Frechede et al, 2006). Variation in intersegmental orientation and overall spinal curvature are modeled implicitly in the current SSM approach; however, explicitly modeling vertebral orientation and spinal curvature variables would allow the investigation of the role and interaction of vertebral morphology, intersegmental orientation, and spinal curvature variables on the likelihood of injury under various loading conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups using idealized parametric models of models with subject-specific geometry have also found that geometry and orientation and material models employed in describing soft-tissue behavior in both cervical spine motion segments lead to differences in the loading response (Kumaresan et al, 1999; del Palomar et al, 2008; Laville et al, 2009; Kallemeyn et al, 2010). In other work, finite element models of the cervical spine were deformed to model gross global changes in curvature (e.g., lordosis, straight, and kyphosis models) based on specified Cobb angle (Frechede et al, 2006). Distributions of strains, forces, and moments along the cervical spine were found to be dependent on loading condition (e.g., vehicular rear-end, frontal, lateral, and oblique impact) and global cervical curvature affected the magnitude of strains, forces, and moments experienced by the spine in all loading directions.…”
Section: Discussionmentioning
confidence: 99%
“…The development of more sophisticated and anatomically accurate models of the human cervical spine using finite element models (FEM) to study cervical-spine injury has provided the motivation for the current study [16][17][18][19][20][21][22][23][24][25][26]. FEM are used to study how variations in initial head/neck posture, cervical-spine curvature, and occupant age/gender/stature affect the likelihood of neck injury in rear MVC, because results of laboratory studies indicate that the likelihood of injury may depend on the initial alignment of the vertebrae [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Different models of the head and neck have been proposed lately with both passive and active muscles (Brolin et al, 2005;Frechede et al, 2005Frechede et al, , 2006Hedenstierna et al, 2009;Fice and Cronin, 2012). However; muscle passive properties are based on data obtained from experiments performed on animal muscles.…”
Section: Introductionmentioning
confidence: 99%